INNOVATIVE TECHNOLOGIES FOR COMPANY MARKETING PROCESS – FROM 4P TO 4E: THE CASE OF LEGO GROUP - Olena Parkhomenko; Olena Iarmosh (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The article is devoted to the experience of using the marketing mix 4E model. The focus of this marketing complex has been redirected from the product to solving the consumer’s problem. The companies shifting from the 4Ps to the 4Es are the ones that will maintain or develop a competitive edge. One of these companies is the LEGO Group. The LEGO brick is the most essential product. The article discusses the principles of the company’s activities based on values and strategies, such as imagination, creativity, fun, learning, caring, and quality. The LEGO brand framework includes belief, mission, vision, idea, values, promises, and spirit. One of the essential products offered by the company is the LEGO SERIOUS PLAY methodology, a creative process designed to enhance innovation and business performance based on using LEGO bricks in work and training. The article considers aspects of applying the traditional marketing model, a mix of 4P and the relatively new 4E model for the company’s products transforming the following components of these models: 1) product becomes experience; 2) place becomes every place; 3) price becomes exchange; 4) promotion becomes evangelism. Through the prism of the 4E model, the company’s mission and vision, market segments that target LEGO products, how the company creates customer experience, features of the development and promotion of the company’s brand, and the values offered to consumers of LEGO Group products are analysed in detail.